2020
DOI: 10.30773/pi.2019.0312
|View full text |Cite
|
Sign up to set email alerts
|

WISC-IV Intellectual Profiles in Korean Children and Adolescents with Attention Deficit/Hyperactivity Disorder

Abstract: Objective This study aimed to compare the Wechsler Intelligence Scale for Children, Fourth Edition (WISC-IV) profiles of children with attention deficit/hyperactivity disorder (ADHD) and typically-developing children (TC) in Korea.Methods The Korean version of the WISC-IV and the Advanced Test of Attention (ATA) were administered to 377 children and adolescents: 224 with ADHD (age 8.2±2.1 years, 182 boys) and 153 TC (age 8.7±2.4 years, 68 boys). Partial correlation and an analysis of covariance were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Although the increase in PSI seems to be a good feature, the increase in WISC-IV index discrepancies with a PSI-induced may lead to impaired functionality. While some of the studies reported that processing speed was impaired mainly in ADHD-I without hyperactivity, other studies reported that processing speed was impaired mainly in hyperactivity/impulsivity symptoms (Brydges et al, 2017; Cook et al, 2018; Ghanavati et al, 2019; Goth-Owens et al, 2010; Kim et al, 2020; Kofler et al, 2019; Molavi et al, 2020; Pievsky & McGrath, 2018; Raiker et al, 2012; Rostami et al, 2020). This may be due to the heterogeneity of ADHD, differences in the materials used in the studies, differences in the factor structure loaded on the tests, or the categorical diagnostic system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the increase in PSI seems to be a good feature, the increase in WISC-IV index discrepancies with a PSI-induced may lead to impaired functionality. While some of the studies reported that processing speed was impaired mainly in ADHD-I without hyperactivity, other studies reported that processing speed was impaired mainly in hyperactivity/impulsivity symptoms (Brydges et al, 2017; Cook et al, 2018; Ghanavati et al, 2019; Goth-Owens et al, 2010; Kim et al, 2020; Kofler et al, 2019; Molavi et al, 2020; Pievsky & McGrath, 2018; Raiker et al, 2012; Rostami et al, 2020). This may be due to the heterogeneity of ADHD, differences in the materials used in the studies, differences in the factor structure loaded on the tests, or the categorical diagnostic system.…”
Section: Discussionmentioning
confidence: 99%
“…In a study comparing ADHD children with normally developed children, it was reported that the WMI and FSIQ scores were lower in the ADHD group. In particular, the low WMI score was considered highly significant (Kim et al, 2020). The fact that WMI was lower than other index scores in our study is consistent with previous studies in ADHD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the ASD-HF group obtains a lower performance in the Processing Speed skill (PSI) than the control group, resulting as the point of weakest in this group. The Working Memory Index (WMI) was significantly lower in SLD and ADHD groups [ 7 , 9 , 13 ] while Processing Speed Index (PSI) was lower in all three clinical groups compared to controls. Furthermore, we found that all three clinical groups have a significantly different profile and a Cognitive Processing Index (WMI + PSI) lower than the General Ability Index (VCI + PRI) compared to typically developing children.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the perceptual reasoning index (PRI) is highest in ASD-HF and the working memory index (WMI) is the lowest in children with typical development [ 3 ]. According to recent studies [ 6 , 7 ] subjects with ADHD, have the average full-scale intelligent quotient score lower than the typically developing children and tend to perform worse on the working memory index (WMI) and on the processing speed index (PSI) than the verbal comprehension index (VCI) and the perceptual reasoning index (PRI). Many studies have demonstrated the usefulness of the WISC-IV scale [ 8 ] to evaluate the cognitive profile of subjects diagnosed with SLD [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%